2016
DOI: 10.1002/pbc.25924
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐6‐Phosphate Dehydrogenase Deficiency in Brazilian Children With Sickle Cell Anemia is not Associated With Clinical Ischemic Stroke or High‐Risk Transcranial Doppler

Abstract: Our study demonstrated that G6PD molecular deficiency was not associated either with clinical ischemic stroke or high-risk TCD. Similarly, we found no associations between G6PD enzyme activity and stroke or high-risk TCD. Small sample size precludes definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The reason for the geographic variations across continents is unclear but may be related to genetic and environmental differences. For example, the presence of alpha‐thalassaemia trait has been associated with lower TCD velocities (Hsu et al , ; Bernaudin et al , ; Cox et al , ; Belisario et al , ), while the concomitant inheritance of glucose‐6‐phosphate dehydrogenase (G6PD) deficiency as well as beta gene haplotypes may have a variable impact on TCD velocities and stroke (Flanagan et al , ; Alsultan et al , ; Cox et al , ; Belisario et al , ). There are emerging data that variation in environmental factors, such as weather and seasonality, as well as prevalence of bacteraemia or nutritional deficiency, such as vitamin D, across regions may underlie the variability of clinical expression of SCA‐related complications (Jones et al , ; Atkinson et al , ; Smith et al , ; Mekontso Dessap et al , ; Tayo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the geographic variations across continents is unclear but may be related to genetic and environmental differences. For example, the presence of alpha‐thalassaemia trait has been associated with lower TCD velocities (Hsu et al , ; Bernaudin et al , ; Cox et al , ; Belisario et al , ), while the concomitant inheritance of glucose‐6‐phosphate dehydrogenase (G6PD) deficiency as well as beta gene haplotypes may have a variable impact on TCD velocities and stroke (Flanagan et al , ; Alsultan et al , ; Cox et al , ; Belisario et al , ). There are emerging data that variation in environmental factors, such as weather and seasonality, as well as prevalence of bacteraemia or nutritional deficiency, such as vitamin D, across regions may underlie the variability of clinical expression of SCA‐related complications (Jones et al , ; Atkinson et al , ; Smith et al , ; Mekontso Dessap et al , ; Tayo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Its effects on cerebrovascular disease are less clear. Some studies indicate no association between G6PD deficiency and stroke or cerebral vasculopathy, 17,23,24 while others do show an increased frequency of magnetic resonance index (MRI)- or transcranial Doppler (TCD)-defined cerebral vasculopathy. 18,25,26 These conflicting data limit the prognostic utility of G6PD deficiency.…”
Section: Determinants Modifiers and Correlates Of Disease Severitymentioning
confidence: 99%
“…In our experience, the prevalence of stroke or high-risk TCD was not significantly different in the groups with and without G6PD deficiency in a retrospective cohort study. 120 This absence of association has been reported in other studies that used molecular analysis as the diagnostic method for G6PD deficiency. 78 , 121 However, Thangarajh et al, 122 showed that the presence of the 376G (rs1050829) or 202A (rs1050828) allele was a significant and independent risk factor for intracranial MRA-arteriopathy in males with SCA.…”
Section: Methodsmentioning
confidence: 61%
“…The 376G allele leads to a very mild reduction in G6PD activity, as demonstrated in one study. 120 Children with the 376G allele (isoform A in males or AA in females) showed 85.2% of the enzymatic activity of G6PD when compared to individuals with the wild 376A allele (isoform B in males or BB in females). On the other hand, studies that reported an association between G6PD deficiency and abnormal TCD or intracranial stenosis used the measurement of G6PD activity as the method to define G6PD deficiency.…”
Section: Methodsmentioning
confidence: 99%